An economical strategy for chromosome walking in the Neurospora crassa pMOcosX library - Frederick J. Bowring; David E.A. Catcheside (Fungal Genetics Reports, 1995)
Chromosome walking using ordered genomic libraries is demanding of both labor and materials. Such libraries are often stored as a set of 96 well microtiter plates with each well containing an individual clone. The library is typically prepared for screening by replicating plates onto ~11 x 7 cm membranes placed on a suitable growth medium. Colonies are lysed in situ and the cellular material washed off leaving DNA bound to the membranes (colony blots). To extend the walk, the library is screened by probing the set of colony blots for homology to sequences close to the terminus identified in the preceding step. Once clones are identified, they are mapped for one or more restriction enzymes, aligned, and a sequence extending the walk in the desired direction is selected to initiate the next phase. The Neurospora crassa genomic library pMOcosX (Orbach 1994 Gene 150:159-162) comprises 50, 96 well microtiter plates. A conventional screening program uses 50 membranes and, due to the practicalities of hybridizing 50 membranes simultaneously, sometimes several rounds of hybridization. In this note we describe a chromosome walking strategy in the pMOcosX library that minimizes the scale of screening and also obviates the need for restriction mapping prior to commencing the next step, which in our experience is a rate limiting factor. We have used this method to establish contigs of 110 and 240 kb on LG V